Arrays of electrically-addressable, optically-transmitting 3D nanostructures on free-standing, flexible polymer films. (26th June 2018) - D'Imperio, L A; McCrossan, A F; Naughton, J R; Merlo, J M; Calm, Y M; Burns, M J; Naughton, M J
Abstract: We describe the fabrication and properties of arrays of optically-transmitting 3D nanocylinders and nanocoaxes on free-standing, flexible, thin films made from a negative photoresist. The fabrication includes mostly standard lithographic techniques, enabled by the use of a release layer that allows separation of the thin film from the substrate in a simple final step. The chemical and mechanical stability of the polymer film and release layer enabled us to produce microstructures by multilayer photolithography as well as subsequent deposition of metal–insulator–metal layers to yield nanoscale coaxial pillars. We demonstrate the robust and flexible qualities of samples in interest of possible uses in wearable electronics and opto-bioelectronic interfacing.